Experimental Study of the Effect of Wire Fiber Addition on the Mechanical Strength of Preplaced Aggregate Concrete - Ngudiyono, .; Akmaluddin, .; Anshari, Buan; Fajrin, Jauhar; Kencanawati, Ni Nyoman; Aqriansyah, M. Yani (Engineering, Technology & Applied Science Research, 2025)
Preplaced Aggregate Concrete (PAC) is a specialized type of concrete, with low tensile strength, making it prone to brittle failure, used in the construction industry. One effective way to enhance durability and minimize cracking is by incorporating fibers into the mix. This study explores the use of wire fibers, produced by cutting wire ropes into pieces approximately 1 mm in diameter and 60 mm in length. Five different concrete mixtures were tested to evaluate the mechanical strength of PAC and Preplaced Aggregate Wire Fiber Concrete (PAWFC). The wire fiber content varied at 0%, 0.25%, 0.5%, 0.75%, and 1% of the total concrete volume, while the proportions of cement, fine and coarse aggregates, water, and Super Plasticizer (SP) remained constant. A mortar mix with a cement-to-sand ratio of 1 and a water-to-cement ratio of 0.45 was used. The mechanical properties, including compressive strength, tensile strength, and modulus of rupture were assessed following the ASTM standards. The results showed that adding wire fiber significantly improved the mechanical strength of PAWFC. Specifically, the optimum 1% wire fiber addition increased compressive strength by 11.23%, tensile strength by 36.85%, and modulus of rupture by 17.23%.